2018
DOI: 10.3389/fped.2018.00351
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Retrognathia and Glossoptosis Does Not Predict Respiratory and Feeding Disorders in Pierre Robin Sequence

Abstract: Pierre Robin sequence (PRS) may lead to life-threatening respiratory and feeding disorders. With the aim to analyse the association of the severities of retrognathia and glossoptosis with those of respiratory and feeding disorders, we retrospectively studied a series of 50 infants with retrognathia, glossoptosis, cleft palate, and airway obstruction. The patients were managed from birth to at least 6 years of age by a single pediatric team at the Armand Trousseau Hospital in Paris within a 12 years period (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 41 publications
(49 reference statements)
0
25
0
1
Order By: Relevance
“…This conclusion aligns with the current pathophysiologic understanding of upper airway obstruction in PRS. Since the publication of a seminal paper by Sher in 1992, it has been understood that although micrognathia-associated glossoptosis underlies the airway obstruction in all patients with PRS to some extent, clinical airway obstruction is determined by a number of causes, including neurologic dysfunction, rate of neuromuscular maturation, and laryngomalacia (Randall et al, 1965; Sher, 1992; Morice et al, 2018). Additionally, Runyan et al (2018) published a retrospective analysis of 171 patients with PRS and found that the most significant factor predictive of surgical intervention was a high obstructive index on preintervention sleep study; the authors noted no differences in micrognathia between patients managed conservatively and those managed surgically ( P = 1.000) (Runyan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion aligns with the current pathophysiologic understanding of upper airway obstruction in PRS. Since the publication of a seminal paper by Sher in 1992, it has been understood that although micrognathia-associated glossoptosis underlies the airway obstruction in all patients with PRS to some extent, clinical airway obstruction is determined by a number of causes, including neurologic dysfunction, rate of neuromuscular maturation, and laryngomalacia (Randall et al, 1965; Sher, 1992; Morice et al, 2018). Additionally, Runyan et al (2018) published a retrospective analysis of 171 patients with PRS and found that the most significant factor predictive of surgical intervention was a high obstructive index on preintervention sleep study; the authors noted no differences in micrognathia between patients managed conservatively and those managed surgically ( P = 1.000) (Runyan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Runyan et al (2018) published a retrospective analysis of 171 patients with PRS and found that the most significant factor predictive of surgical intervention was a high obstructive index on preintervention sleep study; the authors noted no differences in micrognathia between patients managed conservatively and those managed surgically ( P = 1.000) (Runyan et al, 2018). Morice et al (2018) have also reported that grades of retrognathia and glossoptosis are not predictive of respiratory and feeding disorder severity in both patients with syndromic and nonsyndromic PRS (Morice et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars believe that nutritional changes should be studied independently with airway changes, because breathing and swallowing difficulties in PRS patients may not only be related to anatomical variation (such as micrognathia and glossoptosis etc. ), but also to abnormal laryngeal development, neurological disorders, and various other associated syndromes (27). For this part of the patients, high-calorie feeding should be applied as soon as possible (28), instead of waiting for the relief of airway symptoms to bring an improvement in nutrition status; the nutritional risk of PRS may not be accompanied by dyspnea, since the symptoms can appear immediately after birth, or may be delayed (29).…”
Section: Discussionmentioning
confidence: 99%
“…[13] Pierre Robin sendromu gibi genetik hastalıklara eşlik edebilir. [14] Temporomandibüler eklem rahatsızlıkları, yeme ve çiğneme bozuklukları ve görsel bozukluklara yol açabilir. Özellikle yan açıdan görsel görünüm bozukluklarına neden olabileceği gibi rinoplastinin yanı sıra yapılan mentoplasti ameliyatlarının sık nedenidir.…”
Section: İstatistiksel Analizunclassified